Analytical validation and reference intervals for a commercial multiplex assay to measure five novel biomarkers for acute kidney injury in canine urine. (October 2021) - Davis, Jennifer; Raisis, Anthea L.; Miller, David W.; Hosgood, Giselle L.; Rossi, Gabriele
Abstract: Novel urinary biomarkers are increasingly utilized for the diagnosis of acute kidney injury (AKI) in dogs. Magnetic-bead based immunoassays for the simultaneous measurement of multiple biomarkers represent a potentially efficient and cost effective tool for investigators; however there is limited data to support their reliable use in dogs. Analytical validation of a commercial multiplex assay for the measurement of five AKI biomarkers: clusterin, cystatin C, kidney-injury molecule 1 (KIM-1), monocyte chemoattractant protein 1 and neutrophil gelatinase-associated lipocalin (NGAL) in canine urine was performed. The effect of pre-analytical factors including potential interfering substances and sample storage methods were investigated. Urine from 110 healthy dogs was used to determine reference intervals for each biomarker measured, according to American Society of Veterinary Clinical Pathology guidelines. Additionally, urine from 21 dogs with pyuria was used to evaluate the impact of pyuria on biomarker concentration. The assay performed with acceptable accuracy and precision for the measurement of NGAL only. Clinically relevant urine concentrations of bilirubin, haemoglobin, and synthetic colloid solutions led to interference (mean percentage difference > +/− 15% compared to control) with measurement of all or some of the biomarkers. All biomarkers were stable in urine stored at 20–22 °C for 2 h, 4 °C for 12 h, or -20 °C for 6 months. Reference intervals could not be established for KIM-1 due to unacceptable measurement imprecision (intra- and inter assay coefficient of variation 45% and 20% respectively). Urine NGAL concentration was significantly elevated in pyuria ( P < 0.001). Highlights: Multiplex assay was validated for measurement of five renal biomarkers in canine urine. Accuracy and precision was acceptable only for neutrophil gelatinase-associated lipocalin. This assay is not recommended for measurement of kidney injury molecule 1 in canine urine. There were some effects of sample storage and interferents on measurement of all biomarkers. Reference intervals are reported for four renal biomarkers from a population of 110 healthy dogs.